Mapeamento de correspondências hidrofóbicas em complexos serino peptidases e inibidores proteicos através da varredura de agrupamento espectral - Nilma Rodrigues Alves (2015)
In the formation of protein-protein complexes, hydrophobic interactions play an important role in molecular recognition. In this study, the hydrophobic correspondences between serine peptidases surfaces and their protein inhibitors were analyzed. Each hy- drophobic patch was determined at atomic level featuring atoms previously classified as polar and non-polar, and organized in a graph contact network. Both the mapping of the interfaces and the weight of the interactions between peptidase atoms with their respec- tive inhibitors were set by the Silveira-Romanelli (SR) methodology, based on the areas of contacts. In order to identify correspondences, the spectral clustering using normalized Laplacian matrices was applied. These matrices represented 36 non-redundant complexes of trypsin-like and subtilisin-like enzymes and their respective inhibitors, PDB filtered, with information from MEROPS and PFAM. By means of a sweep carried out altering the number of clustering and considering the silhouette coefficient as a measure of their quality, it was possible to reach a general model, in which each complex shows from 2 to 6 complementary hydrophobic regions between enzyme-inhibitor. Such hydrophobi- city inherent to all regions could help explain the success of SCHECHTER & BERGER - 1967’s pioneering work, which used polyalanines (an entirely hydrophobic peptide) as probes for the first mappings of the interfaces in peptidases. In the 36 analyzed com- plexes, the regions also seem to form a hydrophobic ring or semi-annular superstructure, resembling the O-rings identified by BORGAN & THORN - 1998, in their classic paper on the organization of hot spots in protein-protein interfaces. This hydrophobic ring- like superstructure in enzymes might affect solvation water, interfering with the pattern of fluctuation of the solvent local density, a fundamental aspect for the protein-protein complexes, as shown by CHANDLER - 2005 and other authors.